Biomarkers of Sepsis-Induced Acute Kidney Injury. (24th April 2018) - Wang, Kaifei; Xie, Sheling; Xiao, Kun; Yan, Peng; He, Wanxue; Xie, Lixin
Abstract : Sepsis, an infection-induced systemic disease, leads to pathological, physiological, and biochemical abnormalities in the body. Organ dysfunction is caused by a dysregulated host response to infection during sepsis which is a major contributing factor to acute kidney injury (AKI) and the mortality rate for sepsis doubles due to coincidence of AKI. Sepsis-induced AKI is strongly associated with increased mortality and other adverse outcomes. More timely diagnosis would allow for earlier intervention and could improve patient outcomes. Sepsis-induced AKI is characterized by a distinct pathophysiology compared with other diseases and may also have unique patterns of plasma and urinary biomarkers. This concise review summarizes properties and perspectives of the biomarkers for their individual clinical utilization.